The Lesson of Enron for the Future of MDPs: Out of the Shadows and into the Sunlight - Burnele V. Powell (Washington University Law Quarterly, 2002)
There are lessons to be learned from the Enron debacle, at least to the extent that one is seeking insights about the continuing debate over “when”—and not “whether”—multidisciplinary practice (MDP) rules will finally come to the legal profession. In short, I want to remind the profession about what it already knows about this scandal and, most scarily of all, what we do not yet know. Contrary to the kind of knee-jerk, head-in-the-sand response that usually accompanies pleas for reform, I predict that, despite what may be the legal profession’s initial reaction, the Enron scandal will eventually prove to be a catalyst for lawyer multidisciplinary practice reform. This reform will be second only to the reform of the accountants’ auditing/consulting rule mentioned above. I assert, second, that upon the conclusion of the Enron debacle, each of the rationalizations to which opponents of MDP pointed two years ago will have proven demonstrably false in the real-life test of Enron. Third, and finally, I assert that the one thing that will become clear when the dust settles after Enron is that if the legal profession had put the multidisciplinary practice safeguards in place two years ago when it had the opportunity to do so, Enron would probably not have happened.
Keywords: Multidisciplinary practices; Enron Corp.; Conflicts of interest (Lawyers); Multidisciplinary law firms